BS EN IEC 63171-1. Connectors for electrical and electronic equipment. Part 1. Detail specification for two-way, shielded or unshielded, free and fixed connectors. Mechanical mating information, pin assignment and additional requirements for Type 1 copper LC style (25th June 2021) - British Standards Institution,
No abstract available